La cronología de ιγα con subjuntivo en expresión de mandato: La lengua de Sófocles, Eurípides y Jenofonte
In this paper the author tries to point out that ina with subjunctive as imperative is previous to koiné. Likewise he tries to explain its origin and phases starting from a grammaticalization process that is noticeable in the language of Sophocles, Euripides and Xenophon., journal=Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, author=Labiano Ilundain, Juan Miguel, year=2008, month=Apr., pages=55–72